Effect of Torrefaction Temperature, Residence Time and Particle Size on the Properties of Torrefied Food Waste - Ruwaida Abdul Rasid; Thye Mei Chin; Mazni Ismail; Nahsya Nur Udzaifah Abdul Rahman (Indonesian Journal of Chemistry, 2019)
Municipal solid waste (MSW) in Malaysia mainly consists of food waste. As food waste is of organic compounds, its improper management may cause serious environmental issues, as it may produce greenhouse gases and polluting leachate. Alternative management of the food waste is through its utilization. However, the main issue in the utilization of food waste is its heterogeneity, whereby the diversified cooking methods, as well as food origin, emanates different characteristics. Hence, food waste needs to be pre-treated through the torrefaction process, which is a thermochemical method that converts it to biochar at a temperature between 200–300 °C in an inert environment. The main aim of this work is to evaluate the feasibility of food waste as a potential source of energy through the torrefaction process. The torrefaction of food waste was conducted in a vertical tubular reactor under an inert atmosphere. The results obtained from this study showed that as torrefaction temperature became more severe, the produced torrefied solid is more energy-dense, with apparent higher fixed carbon content and improved heating values. These findings imply that food waste may be able to be utilized as a solid biofuel, with fuel properties comparable to conventional fuels.